Kahoot-Based Learning Game to Improve Mathematics Learning Motivation of Elementary School Students - Setiawan, Adi; Soeharto, Soeharto (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
Mathematics is an important lesson for elementary school students. However, mathematics is usually identified as difficult, unenjoyable and boring. Teachers need to motivate the students that mathematics can be fun. One media that could be used is Kahoot. This study aimed to apply Kahoot-based learning games. To improve mathematics learning motivation for the fourth-grade elementary school students. This study is classroom action research (CAR). It was carried out in two learning cycles using the Kemmis and Taggart model. The subjects of this study were the fourth-grade elementary school students in the second semester of the 2018/2019 academic year consisted of 28 students. The research data were obtained through interviews, mathematics learning achievement tests, learning observation sheets, and field notes. Data analysis was carried out qualitatively and supplemented by quantitative analysis. The results showed that students' mathematics learning motivation could be improved through Kahoot-based learning games. Students’ test results showed an increase in learning motivation by 19.85 or 44.55%. The results of this study provide information for teachers, schools, and researchers to improve students’ learning motivation through Kahoot-based learning game.